Implementation of BPJS Kesehatan Policy and Its Challenges in Indonesia - Aulia Wanda Fitria; Martin Luther Giawa; Muhamad Nurul; Nimas Elka Pratiwi; Shifa Kusuma Wardani (JURNAL ILMIAH ILMU ADMINISTRASI, 2025)
The National Health Insurance (JKN) program, administered by the Health Social Security Administering Agency (BPJS Kesehatan), is one of the Indonesian government's strategic policies aimed at ensuring citizens' fundamental right to healthcare and achieving Universal Health Coverage (UHC). Since its implementation in 2014, this policy has significantly expanded membership coverage and improved public access to healthcare services. Nevertheless, the implementation of the BPJS Kesehatan policy continues to face various structural and operational challenges. This study aims to analyze the implementation of the BPJS Kesehatan policy in Indonesia and identify the major challenges encountered during its implementation. The research employed a qualitative descriptive approach through a literature review of accredited national journal articles and relevant policy documents. The findings indicate that although BPJS Kesehatan has successfully enhanced access to healthcare services, its implementation remains constrained by limited human resources, disparities in healthcare facilities across regions, complex administrative procedures, and the public's limited understanding of BPJS Kesehatan service mechanisms. Based on policy implementation theory, the analysis reveals that communication, resources, implementers' disposition, and bureaucratic structure are the key determinants of successful policy implementation. This study recommends strengthening cross-sectoral collaboration through the pentahelix model as a strategic approach to improving the effectiveness, quality, and sustainability of BPJS Kesehatan policy implementation in Indonesia.